2016
DOI: 10.5455/msm.2016.28.333-337
|View full text |Cite
|
Sign up to set email alerts
|

Side to Side Differences Between Dominant and Non-dominant Arm's Bone Density and Isometric Handgrip Strength in Males and Females Aged 40-65 Years Old

Abstract: Objective:This observational, cross-sectional study, investigates and compares the differences of BMD, T-score, Z-score and isometric strength between dominant (D) versus non-dominant (ND) arms of 162 subjects aged 40-65 in a developing, low income country (Kosova).Material and Methods:Bone Mineral Density (BMD), T-score and Z-score at distal forearm regions of both arms (measured by DXA scan), together with the Handgrip Isometric Strength (HIS) (by handgrip) were evaluated in a total subjects (53 Males and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Participants characteristics as shown in our previous study 17 , resulted in no differences observed in age and weight between male (55.15±7.12 and 78.21±13.25, respectively) and female participants (54.27±5.1 and 75.52±11.01, respectively), and significant differences in height and body mass index (BMI) between males (173.06±7.51 and 26.05±3.73, respectively) and females (164.52±5.58 and 27.95±4.36, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants characteristics as shown in our previous study 17 , resulted in no differences observed in age and weight between male (55.15±7.12 and 78.21±13.25, respectively) and female participants (54.27±5.1 and 75.52±11.01, respectively), and significant differences in height and body mass index (BMI) between males (173.06±7.51 and 26.05±3.73, respectively) and females (164.52±5.58 and 27.95±4.36, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…PA level was measured with self-administered IPAQ (International Physical Activity Questionnaire) by weighting each type of activity by its energy requirements (MET) for the last seven days, translated and updated in Albanian from Boshnjaku A et al 15,16 Based on this questionnaire, all the subjects were classified on three groups according to the level of PA (low, moderate and high). 15 Listed questionnaires were previously translated and validated in Albanian by Boshnjaku et al (2015) and Krasniqi E et al (2016). Every participant was interviewed through filling these questionnaires.…”
Section: Assessments Of Drug Usage the Level Of Physical Activity Amentioning
confidence: 99%
“…It is challenging to compare this study to previous studies on osteoporosis because few have reported the association between osteoporosis and HGS; while several studies showed the relationship between osteoporotic fracture and HGS, 14 - 16 , 35 ) they did not use RHGS by applying BMI; therefore, they did not completely prove the role of HGS. Moreover, they used only HGS without considering the dominant hand.…”
Section: Discussionmentioning
confidence: 87%
“…Although there are differences in disease, our results are is similar to those of previous studies reporting a significant association only in the left hand. In their observational, cross-sectional study of the differences in BMD, T-score, Z-score at distal forearm regions of both arms and handgrip isometric strength between dominant versus non-dominant hands in 162 subjects aged 40–65 years, 35 ) the authors reported significantly higher BMD, T-score, Z-score, and handgrip isometric strength in the dominant hand than those in the non-dominant hand among women aged 40–65 years (p<0.05). This finding suggests that there is also a significant difference in baseline values between non-dominant and dominant hands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation